Proyecto Frijol Zona Andina: Antropologia: Informe final - Maître, Adrian (International Center for Tropical Agriculture, 1990)
Anthropological work carried out by the PROFRIZA project in Cusco over 2 cropping seasons, between 1988-90, are reported. The status of bean cultivation in the region was assessed, as well as the experience acquired in seed production, small farmer management of farming activities, and the integration of farming communities that have old ways of exchanging products and services. Appropriate technology to promote crop improvement was identified, and crop management aimed at achieving good results on just one field, instead of several fields, and perhaps with low yields. When associated with maize, bean yields were low; an alternative would be to search for improved bean lines. Seed production in the Andean region should facilitate the diffusion of improved var. and solve the problem of seed availability, while maintaining seed quality. (CIAT)